Irrigation infrastructure quality management system toolkit for Sub-Saharan Africa using Ethiopia, Kenya and Uganda as a case study: technical report - Hailu, H.; Abdella, Y.; Seid, Abdulkarim; Haileslassie, Amare (International Water Management Institute, 2024)
Sub-Saharan African (SSA) countries have identified small-scale irrigation development as a priority to ensure food security and improve agricultural production. However, they have encountered challenges related to inadequate planning, study, design and inferior-quality construction of irrigation infrastructure. To bridge these quality gaps, the concept of developing a quality management system (QMS) toolkit was initiated by the Food and Agriculture Organization of the United Nations (FAO) in collaboration with the International Water Management Institute (IWMI). The objective of the toolkit is to establish a management framework that directs and controls small-scale irrigation development processes in SSA as per contractual requirements, quality standards and governing regulations to ensure quality outputs in all development phases. Ethiopia, Kenya and Uganda were chosen as focal countries. Two approaches were employed to develop the toolkit. A literature review on quality management practices in irrigation development within the focal countries and global experiences was conducted to learn lessons and identify parameters that have key roles in quality management practices. This was followed by case studies and analyses of irrigation development practices in each focal country through stakeholder consultations, project site observations and focus group discussions. Based on the findings, a toolkit with a comprehensive set of guidelines, checklists, templates and resources was developed. The toolkit is presented in two volumes. Volume I is the toolkit guidelines, which cover the goals and scope of the toolkit along with details of the approaches employed and the findings from the development process. It also presents the proposed checklists, tools, templates and forms. It briefly explains how to use them to conduct quality management in small-scale irrigation project (SSIP) development. Volume II includes the key parameters and to-do lists segregated by development phases, stages, components and subcomponents of the SSIP development process. It also includes proposed institutional arrangements for implementing the QMS initiative by the focal countries. Furthermore, a user-friendly webpage was developed to allow for quick access to various additional open-source resources, including guidelines, standards and best practices. The toolkit aims to help governments and other implementers introduce an effective quality management system in the irrigation development process adapted to country-specific irrigation regulations and standards. For effective implementation of the toolkit, the commitment of the implementing organizations, institutionalizing quality management in project development and regular capacity building of implementing agents are recommended.